Trends in Body Mass Index and Obesity Prevalence among School Going Students with Down Syndrome in Islamabad and Rawalpindi - Ibtesam-E-Fajar, Huma Bashir Janjua, Taimur Khalil Sheikh, Daniyal Ahmed, Iman Baig, Sundus Asghar Baig, Aamna Khokhar (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Down syndrome is present in every 1 in 700 births, associated with developmental disability and comorbidities, like obesity which significantly contributes to morbidity and mortality in these children. Objective: To identify the trends in body mass index and prevalence of obesity in school going down syndromes. Methodology: A descriptive cross-sectional survey conducted at special children’s schools in Islamabad and Rawalpindi. A questionnaire was designed after literature search and was filled by the parents of the selected candidates according to inclusion criteria i.e., school going down syndromes and residents of Islamabad and Rawalpindi, in an interactive counselling session conducted by authors in collaboration with pediatrician, with parents at respective schools of their child, keeping the questionnaire anonymous. After data collection it was entered in SPSS v25 for statistical analysis in terms of frequencies and percentages. Results: Our survey included 44 candidates in which majority was between the age group 11 years to 20 years i.e., 52% (n=23) and 27% (n=12) were below 10 years. This survey showed that 95% (n=42) of our selected candidates have Normal BMI while 4.5% (n=2) of our candidates fall in Overweight (High BMI) category. Conclusion: Most of our selected Down syndrome individuals are protected from obesity as they indulge in different sports, physical activities, physiotherapy and maintain a balanced diet. It is therefore recommended to emphasize the importance of physical activities, active participation in sports, gymnastics, regular exercises and maintaining a healthy diet plan to avoid obesity in these individuals so that further complications of obesity can be prevented thus improving the quality of life of these individuals.